High‐Performance Cobalt Selenide and Nickel Selenide Nanocomposite Counter Electrode for Both Iodide/Triiodide and Cobalt(II/III) Redox Couples in Dye‐Sensitized Solar Cells. Issue 6 (22nd April 2014) - Wang, Zaiwei; Xu, Hongxia; Zhang, Zhongyi; Zhou, Xinhong; Pang, Shuping; Cui, Guanglei
Abstract The nanocomposites of cobalt selenide and nickel selenide (Co0.85Se/Ni0.85Se) were successfully fabricated on FTO glass by a facile co‐electrodeposition method at ambient temperature. Nanocomposite films were used as electrocatalysts in dye‐sensitized solar cell counter electrodes for regeneration of both iodide/triiodide and cobalt(II/III) redox couples. Co0.85Se/Ni0.85Se were mainly composed of nanoflakes and nanoparticles. It is noted that such nanostructure generated by nanoparticles embedded with 2D nanoflakes led to high active sites and was accessible to cobalt(II/III) electrolyte, delivering better catalytic activity for the reduction of larger volume cobalt(II/III). As a result, for cobalt(II/III) electrolyte, the Co0.85Se/Ni0.85Se based dye‐sensitized solar cell performed significantly improved efficiency than that of Pt and Co0.85Se. Meanwhile, the Co0.85Se/Ni0.85Se based dye‐sensitized solar cell held comparable energy conversion efficiency to that of Pt and Co0.85Se for iodide/triiodide electrolyte.